Acceleration Number of Head Lectors Through The Intervention of The Model of Paper Sosio Transformis - Rustiadi, Tri (Universitas Negeri Semarang, 2018)
The result of preliminary study conducted through interview and documentation study of personnel and general equipment in FIK in January 2017, found the number of lecturers with the position of Lektor in Faculty of Sport Science (FIK) amounting to 33. Of 33 lecturers when viewed from time to occupy the position and education owned there are 16 lecturers who should have proposed to the position of Head Lector. The formulation of the problem in this research is “How is the effectiveness of focused mentoring model in acceleration effort to increase to Head Lector’s Position and what are the obstacles faced in the field related to model intervention. The research method was done by qualitative approach, the informant was determined by purposive sampling technique and then the informant was added with the snowball technique. With purposive sampling technique, there were 10 people as informant. The research instruments are in-depth interview guide and observation guide, and data analysis technique using analysis model from Miles and Huberman.The result of this research get the effectiveness value of model 30% (not effective), this happened because of the characteristics of departments in FIK. Inhibiting factors in increasing the human resources of lecturers to the position of Head Lecturer in the field of public health and sports on FIK Unnes have different characteristics. In the field of public health, the main constraint is in the field of educational activities, where the IKM department is a relatively new department and with human resources who are still in S3 studies (33%). Increasing human resources to the position of Head of Sports sector, the obstacle that needs to get the main attention is the publication to the journal, this is exacerbated by low motivation, although there are 5 lecturers who have passed the S3. Characteristics of each field in this FIK require a mentoring model to be able to improve the quality of human resources, especially to Head Lector